Global value chains: Measurement, trends and drivers - Simone Cigna; Vanessa Gunnella; Lucia Quaglietti (European Central Bank (ECB), 2022)
Global value chains (GVCs) have shaped the dynamics of globalisation in recent years. This paper reviews key concepts and tools to measure countries' involvement in GVCs, explores recent trends and investigates the underlying drivers of GVC participation empirically. The analysis in the paper finds that in the last decade, GVCs have undergone an important transformation, with participation falling on the back of rising trade costs and the trade integration of some large emerging market economies slowing, while the role of recent technological developments remains unclear. In addition, supply chains appear to have become increasingly regional over time. The paper also offers an insight into the role of production chain linkages in the transmission of recent global shocks across countries, uncovering important amplification effects on trade and activity. Finally, it discusses future prospects for GVCs and global trade, including in the light of developments associated with the coronavirus pandemic.
Keywords: F13; F14; F15; F23; F62; 330; global value chains; globalisation; trade slowdown; gravity equation; COVID-19